2022
DOI: 10.1155/2022/4098271
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TP73-AS1 Exacerbates the Non-Small-Cell Lung Cancer (NSCLC) Process via Regulating miR-125a-3p-Mediated ACTN4

Abstract: Background. LncRNA TP73-AS1 has been revealed to exert a noteworthy impact on the occurrence and advancement of different cancers. In this study, we explored the function of TP73-AS1 in tumor growth, cell progression as well as the relevant molecular mechanism in non-small-cell lung cancer (NSCLC). Methods. QRT-PCR was employed to assess the expression of TP73-AS1, miR‐125a-3p, and actinin alpha 4 (ACTN4) in NSCLC cells. The biological effect of TP73-AS1 on NSCLC cells was assessed by cell transfection, CCK8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Wan et al focused on circ_0002483 accelerating lung adenocarcinoma progression by targeting miR-125a-3p, while miR-125a-3p mimic counteracted the cancer-promoting effect of circ_0002483 [ 25 ]. Tong et al also observed that TP73-AS1/miR-125a-3p/ACTN4 regulatory network could mediate the occurrence and development of NSCLC, and miR-125a-3p inhibitor reversed the inhibitory function of silencing TP73-AS1 on tumor growth [ 26 ]. In this study, we illustrated that the migration and invasion levels of cells were restored after transfection with miR-125a-3p inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Wan et al focused on circ_0002483 accelerating lung adenocarcinoma progression by targeting miR-125a-3p, while miR-125a-3p mimic counteracted the cancer-promoting effect of circ_0002483 [ 25 ]. Tong et al also observed that TP73-AS1/miR-125a-3p/ACTN4 regulatory network could mediate the occurrence and development of NSCLC, and miR-125a-3p inhibitor reversed the inhibitory function of silencing TP73-AS1 on tumor growth [ 26 ]. In this study, we illustrated that the migration and invasion levels of cells were restored after transfection with miR-125a-3p inhibitor.…”
Section: Discussionmentioning
confidence: 99%